2006
DOI: 10.1109/mcg.2006.140
|View full text |Cite
|
Sign up to set email alerts
|

Visuohaptic simulation of bone surgery for training and evaluation

Abstract: Visual and haptic simulation of bone surgery can support and extend current surgical training techniques. The authors present a system for simulating surgeries involving bone manipulation, such as temporal bone surgery and mandibular surgery, and discuss the automatic computation of surgical performance metrics. Experimental results confirm the system's construct validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(86 citation statements)
references
References 5 publications
0
83
0
3
Order By: Relevance
“…32 One popular use for hapticsenabled surgical robots is in the training and assessment of surgery residents. [33][34][35][36] It has been shown that such systems can be useful for improving surgical skills and for assessing the proficiency of the trainees. However, the most important application of haptics-enabled systems is in the actual operating room, where the surgeon performs delicate procedures that require precise and accurate sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…32 One popular use for hapticsenabled surgical robots is in the training and assessment of surgery residents. [33][34][35][36] It has been shown that such systems can be useful for improving surgical skills and for assessing the proficiency of the trainees. However, the most important application of haptics-enabled systems is in the actual operating room, where the surgeon performs delicate procedures that require precise and accurate sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combined hapticvisual training modes have an advantage over either haptic or visual modes alone for tasks that have a force component, such as surgical simulation [15]. However, limitations to surgical training with a haptic feedback simulator were reported in one study; even though haptic feedback enabled a significant improvement in a laparoscopic suturing and knot-tying task with a higher learning rate, the surgeons reached a plateau after 5 h of training with the haptic device [16].…”
Section: Discussionmentioning
confidence: 99%
“…Their model is simple, fast to compute and fits quite well with experimental data. The geometry of the drill is assumed to be a sphere but Morris et al [13] proposed a more complete erosion rate model based on sample points on the drill tool. An other milling model is also proposed in [14].…”
Section: Previous Workmentioning
confidence: 99%